The differential impact of motivational climate on adolescents' psychological and physiological stress responses. (May 2017) - Hogue, Candace M.; Fry, Mary D.; Fry, Andrew C.
Abstract: Objectives: The purpose of this study was to investigate whether motivational climates have a differential impact on adolescent psychological and physiological stress responses (i.e., salivary cortisol). It is important to investigate this relationship, as psychological stress and stress-responsive hormones have been implicated in a variety of biochemical processes deleterious to mental and physical health. Although youth consistently respond positively to caring, task-involving (C/TI) physical activity settings, ego-involving (EI) climates remain prevalent in youth sport contexts. Design: Middle school students ( N  = 47) were separated by gender and randomly assigned to either a C/TI or EI 30 min instructional juggling session. Method: Salivary cortisol was measured at four times over the 3 h study, including one baseline ( t  = 0 min; juggling session start) and three response measures ( t  = +30, t  = +45, and t  = +60 min). Psychological stress and motivational responses were also examined, including anxiety, affect, enjoyment, and effort. Individual items were utilized to substantiate stress perceptions and assess psychological responses. Results: Results revealed EI climate procured a significant rise in salivary cortisol and greater humiliation, self-consciousness, shame, negative affect, and anxiety, relative to the C/TI group, while adolescents in the C/TI group responded more favorably (e.g., greater effort and enjoyment). Conclusions: These findings suggest the motivational climate can differentially impact adolescents' stress responses, with EI climates eliciting both physiological and psychological stress responses in youth. In contrast, C/TI climates may buffer performance related stressors that accompany group achievement settings and yield a protective response. Highlights: Ego-involving motivational climates (EIMCs) triggered a rise in salivary cortisol. Youth experienced shame and embarrassment while learning a new skill in an EIMC. Youth in EIMCs reported more negative mood states and higher stress responses. Caring, task-involving motivational climates (CTIMCs) elicit protective responses. CTIMC youth reported better moods and higher effort and enjoyment than EIMC youth.